IMPACT OF DIFFERENT ZINC APPLICATION METHODS AND PHOSPHORUS DOSES ON GROWTH, YIELD AND GRAIN ZINC CONTENTS OF WHEAT - SHAHBAZ, MA; ZAFAR, M; AZIZ, S; ULLAH, F; TARIQ, M; UMAR, F; SATTAR, A; KHOKHAR, MI; TIPU, ALK; ALAM, S (Biological and Clinical Sciences Research Journal, 2024)
Wheat is a staple crop of around half of the world’s population. About 30 percent of the world’s population is suffering from Zn deficiency. Zn deficiency problems can be encountered by agronomic and genetic biofortification. Phosphorus (P) is an important plant macronutrient and has an antagonistic relationship with Zn. A field study was performed to evaluate the impact of different Zn application methods and P doses on growth, yield, and grain Zn contents of wheat at the Agronomic Research Farm, University of Agriculture Faisalabad, Pakistan, using a high accumulation wheat variety Zincol-2016. Three doses of P (100, 150, and 200% of recommended P) along with three Zn application methods (seed priming, soil mixing, and foliar application) were applied to wheat using randomized complete block design (RCBD) with three replicates under split-plot arrangement. All agronomic practices were kept normal and uniform for all treatments. Parameters including growth, yield, and Zn content in wheat grains were monitored using standard protocols. The results were evaluated using Fisher’s analysis of variance at a 5% probability level. A comparison of means of treatments was performed using the least significant difference (LSD) test. The highest value of SPAD reading (56.38) was noted in treatment where Zn was applied as priming and P was applied at 200%. Maximum crop growth rate (63.17) was observed in P3 where Zn was applied as mix in soil. Maximum spike length (14.25), spikelets per spike (17.67), and Zn concentration were observed in P3 as a result of foliar application of Zn. Highest grain weight per spike (1.89g), no. of tillers (691.01), grain yield (4.09 t ha-1), biological yield (11.01 t ha-1), harvest index (36.54%) and NDVI (0.42 were observed in P3 where Zn was applied as soil mix.